2020
DOI: 10.1055/a-1096-1592
|View full text |Cite
|
Sign up to set email alerts
|

Erfolgreiche intraduktale Radiofrequenzablation residuellen Adenomgewebes nach endoskopischer Papillektomie

Abstract: ZusammenfassungDie Behandlung von Adenomen der Papilla duodeni major stellt für den Endoskopiker oft eine Herausforderung dar. Wir berichten über zwei Patienten mit Papillenadenomen, die nach endoskopischer Papillektomie jeweils zentral im Bereich der Mündung des Ductus hepatocholedochus ein Restadenom aufwiesen. Bei fehlender Möglichkeit einer weiteren endoskopischen Resektion erfolgte eine intraduktale Radiofrequenzablation anstelle einer chirurgischen Sanierung. Im Rahmen der Nachsorge ergaben sich weder ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A single session of RFA eradicated dysplasia in 70% patients at 12 months follow up. Biliary strictures requiring temporary biliary stenting occurred in 21% patients following RFA [42,43]. Cho et al…”
Section: Management Ampullary Adenomasmentioning
confidence: 99%
See 1 more Smart Citation
“…A single session of RFA eradicated dysplasia in 70% patients at 12 months follow up. Biliary strictures requiring temporary biliary stenting occurred in 21% patients following RFA [42,43]. Cho et al…”
Section: Management Ampullary Adenomasmentioning
confidence: 99%
“…A single session of RFA eradicated dysplasia in 70% patients at 12 months follow up. Biliary strictures requiring temporary biliary stenting occurred in 21% patients following RFA [42,43]. Cho et al [44 ▪▪ ] reported good long term clinical success rates of RFA in treating residual or relapsed ampullary adenomas with intra ductal extension.…”
Section: Managementampullary Adenomasmentioning
confidence: 99%